IMPLEMENTASI PEMBELAJARAN KITAB TA’LIM MUTA’ALLIM DALAM MEMBENTUK KEDISIPLINAN SANTRI KELAS XII PONDOK PESANTREN TAHFIDZUL QUR’AN TARBIYATUNA SRAGEN - Rispandi, R; Sukari, S; Sugiyat, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to analyze the implementation of the Ta'lim Muta'allim book learning in shaping the discipline of 12th-grade students at the Tahfidzul Qur'an Islamic Boarding School (PPTQ) Tarbiyatuna Sragen. The research method uses a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The research was conducted on ustadz and 12th-grade students using descriptive-interpretative analysis. The research results show that the implementation of the Ta'lim Muta'allim book learning has a significant impact on student discipline formation through a comprehensive spiritual approach. The internalization process of disciplinary values successfully transformed students' awareness from mere external compliance to meaningful discipline arising from internal consciousness. The research implications indicate that classical book-based Islamic boarding school education methods remain relevant in forming high-quality youth character.